Sequoia the heralded tree in American art and culture - Vermaas, Lori (Smithsonian Books, 2003)
"In a wide-ranging analysis of the cultural meaning of the California sequoias, Lori Vermaas reveals how Americans have seen nature as an inspiration, a natural resource, and a national treasure. Analyzing a wide range of sources - landscape paintings, stereographs, tourist photographs, advertisements, and art photography - Vermaas traces the transformation in American views of the natural environment from the nineteenth century to today." "When Americans first explored the Sierras and saw the sequoias in 1852, they were awestruck. They viewed these trees not just as wonders of nature but as American possessions - symbols of the nation's strength, nobility, and endurance - whose significance was made more poignant by the sectional issues that threatened the nation's very foundation. Lacking an ancient history and troubled by secession scares, Americans turned to the landscape for signs of a durable heritage